Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1021/pr301067r
|View full text |Cite
|
Sign up to set email alerts
|

The Shotgun Proteomic Study of the Human ThinPrep Cervical Smear Using iTRAQ Mass-Tagging and 2D LC-FT-Orbitrap-MS: The Detection of the Human Papillomavirus at the Protein Level

Abstract: The ThinPrep cervical smear is widely used in clinical practice for the cytological and molecular screening against abnormal cells and Human Papillomavirus (HPV) infection. Current advancements made to LC-MS proteomics include the use of stable isotope labeling for the in-depth analysis of proteins in complex clinical specimens. Such approaches have yet to be realized for ThinPrep clinical specimens. In this study, an LC-MS method based on isobaric (iTRAQ) labeling and high-resolution FT-Orbitrap mass spectrom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(42 citation statements)
references
References 51 publications
(73 reference statements)
1
41
0
Order By: Relevance
“…Recently, a study from Papachristou et al, allowed to detect six HPV-derived proteins, including the highrisk HPV16 type, in ThinPrep smear specimens from HPV positive and HPV negative females by a high precision Mud-PIT, iTRAQ labeling and high-resolution FT-Orbitrap MS. These data were also confirmed with PCR-hybridization molecular methods [35].…”
Section: Commentssupporting
confidence: 60%
See 2 more Smart Citations
“…Recently, a study from Papachristou et al, allowed to detect six HPV-derived proteins, including the highrisk HPV16 type, in ThinPrep smear specimens from HPV positive and HPV negative females by a high precision Mud-PIT, iTRAQ labeling and high-resolution FT-Orbitrap MS. These data were also confirmed with PCR-hybridization molecular methods [35].…”
Section: Commentssupporting
confidence: 60%
“…Shotgun analyses are commonly used on a standardized platform to compare proteome differences corresponding to disease phenotypes, molecular characteristics and responses to stimuli [34]. Recently, shotgun proteomics was applied to human thinprep cervical smear using isobaric tag for relative and absolute quantitation (iTRAQ) mass-tagging and 2D LC-FT-Orbitrap-MS [35].…”
Section: Gel-freementioning
confidence: 99%
See 1 more Smart Citation
“…17 The proteomics strategy based on isotopic labeling with isobaric tags for relative and absolute quantitation (iTRAQ) reagents currently allows for the analysis of up to eight different samples simultaneously and quantitative detection of very low-abundance proteins, such as HPVderived proteins from cervical smears. [18][19][20] Previous proteomics studies have identified a number of biomarkers for early diagnosis or prognostication of cervical carcinoma and its precursors. 21 Because high-risk HPV types are frequently detected in most of the cases of cervical carcinoma and precancerous lesions, these biomarkers for cervical carcinoma are possibly associated with the HPV infection.…”
Section: Introductionmentioning
confidence: 99%
“…Proteomic and mass spectrometry technology might be an excellent tool to identify the nuclear factor which binds the HPV-16 In-1. In fact, this technology has been recently used to analyze human Thin Prep cervical smears from normal or cancer tissues, identifying inclusive protein from different HPV types [23].…”
Section: Introductionmentioning
confidence: 99%